Participation in Context: Neighborhood Diversity and Organizational Involvement in Boston. (13th September 2013) - Tran, Van C.; Graif, Corina; Jones, Alison D.; Small, Mario L.; Winship, Christopher
<x xml:space="preserve">Abstract</x> We use unique data from the Boston Non‐Profit Organizations Study, an innovative survey containing rich information on organizational participation across seven social domains in two Boston neighborhoods, to examine the relationship between ethnic diversity and participation in local organizations. In particular, we identify neighborhood‐based social ties as a key mechanism mediating the initial negative association between diversity and participation. In contrast to previous work, we measure participation using both the domain‐based and group‐based approach, with the former approach uncovering a wider range of organizational connections that are often missed in the latter approach. We also investigate the relationship between interpersonal ties and organizational ties, documenting how primary involvement with an organization facilitates the development of further interpersonal ties and secondary forms of organizational involvement. We then discuss implications of our findings for urban poverty research. Participación en Contexto: Diversidad Barrial e Involucramiento Organizacional en Boston (Van C. Tran, Corina Graif, Alison D. Jones, Mario L. Small y Christopher Winship)